Statistic and results in transurethral endoscopic surgery. - Pereyra Bonasso, Jorge; Gayol Collete, Mario; Viola Peluffo, Julio (Cirugía del Uruguay, 1983)
W e report our four ye ar experience in transurethral urological surgery: 399 procedures were made in 316 patients, covering almost ·all the surgical pathology that can appear in adults up to the level of the pelvic ureter, bladder, bladder neck, prostate and urethra. We analize these cases according to its pathology and its transurethral surgery, concluding that our results and our morbi-mortality are similar the those refered in foreing literature,